THE FRIENDSHIP VALUES BETWEEN THE MAIN CHARACTERS AS REFLECTED IN KATHERINE PATERSON’S BRIDGE TO TERABITHIA: A PSYCHOLOGICAL STUDY - Agus Mustajib (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2020)
This research entitled "The Friendship Values between the Main Characters as Reflected in Katherine Paterson’s Bridge to Terabithia: A Psychological Study". This research was intended to find out the friendship values among the main characters of the novel Bridge To Terabithia written by Katherine Paterson. The type of this research was library research, which consists of primary data and secondary data. The primary data of this research were the novel entitled Bridge To Terabithia written by Katherine Paterson, while the secondary data are taken from other sources such as books, journals, articles that are related to the topic, and the internet sources to complete the data. The subject of this research was the novel Bridge To Terabithia, while the object of this research focused on the friendship values between the main characters for life in Katherine Paterson’s Bridge To Terabithia. The methods used in this research were critical reading and documentation. Collecting the data, he does some steps such as reading the novel precisely and intensively, making notes, visiting the library, and exploring the data from the internet which were related to the topic. The researcher found the friendship values of the main characters were caring for others, being helpful, giving respect, giving hope, joys, and inspiring to others.